Involvement of NLRP3 and NLRC4 Inflammasome in Uropathogenic E. coli Mediated Urinary Tract Infections - Verma, Vivek; Gupta, Surbhi; Kumar, Parveen; Yadav, Sonal; Dhanda, Rakesh Singh; Gaind, Rajni; Arora, Renu; Frimodt-Møller, Niels; Yadav, Manisha (Frontiers in Microbiology, 2019)
Background: Inflammatory response during urinary tract infection (UTI) is mediated by innate immune defense. Nod like receptors (NLRs) have been proposed to work simultaneously beside TLR pathways to mediate pro-inflammatory response and maintain tissue homeostasis. Some in-vitro reports have showed the involvement of NLRP3 inflammasome during uropathogenic Escherichia coli (UPEC) mediated UTI. So we have sought to determine the status of various inflammasomes and their components in UPEC mediated UTI. Methods: A total of 186 females experiencing the first episode of UTI were recruited for the study and forty were found to be positive for UPEC (≥105 CFU/ml) in their urine (N= 40). Further, we analyzed the expression of NLRP3, NLRC4, NAIP, AIM2, ASC, CASPASE-4 and CASPASE-1 gene at mRNA and protein level in the blood of UPEC confirmed study subjects through real time qPCR and immunoblotting. Healthy females (N= 40) visiting the OPD for health checkups, family planning advice and subjects undergoing routine medical examinations, were recruited as healthy control subjects. Pro-inflammatory cytokines (IL-6, IL-8, IFN-γ, TNF-α and MCP-1) were measured in the plasma of patients and controls through ELISA. For investigation of the involvement of NLRC4 and NLRP3 inflammasome, in-vitro studies were performed using co-immunoprecipitation and confocal microscopy. Results: Most of the inflammatory regulators studied (i.e. NLRP3, NAIP, NLRC4, ASC and CASPASE-1) were found to be up-regulated at both mRNA and protein levels in the UPEC infected UTI patients. Also, pro-inflammatory cytokines (IL-6, IL-8, IFN-γ, TNF-α and MCP-1) were found to be up-regulated in the patients group. However, no significant difference was observed in the expression of AIM2 and CASPASE-4 genes at both mRNA and protein levels. Further, in-vitro studies have shown the involvement of NLRC4 inflammasome in UPEC infected THP1 derived macrophages. Conclusion: Involvement of NLRP3 and NLRC4 inflammasomes in UPEC infected UTI is evident from our findings. This is the first report showing levels of inflammasome and its components in UTI patients suggesting a possible role during UPEC mediated UTI, which is not reported worldwide till date. We have also reported the involvement of NLRC4 inflammasome for the first time during UTI infection.